The covid-19 pandemic and the psychic impacts on university professors: an analysis from freudian theory (Revista Internacional de Formação de Professores, 2025)
The coronavirus pandemic has generated a series of changes in the course of society as a whole. All social sectors have been impacted, including education, demanding quality in teaching and learning processes, especially with limited space, time, and tools. This article presents the psychological and social impacts on professors at a higher education institution in Cascavel, Paraná. The objective is to identify anguish, symptoms, and helplessness as effects of the pandemic and interpret them based on Freudian psychoanalytic theory. This is a qualitative study developed through the application of a self-administered questionnaire created by the researchers themselves. Thirty-four professors from different fields participating in the Human Connections project participated in the study. The results also revealed that when questions about mental life and educational quality were asked, few responses were obtained relative to the number of professors at the institution, which represents a resistance to psychoanalysis' involvement in its own subjectivity. The historical milestone, pandemic and post-pandemic, forces individuals and the collective to broaden their reflections on which choices are basic and secondary for living.
Keywords: Pandemic. Mental health. Psychoanalytic theory. University environment.